A popular systemic accident model in China: Theory and applications of 24Model. (March 2023) - Wu, Yali; Fu, Gui; Wu, Zhirong; Wang, Yuxin; Xie, Xuecai; Han, Meng; Lyu, Qian
Highlights: The systemic 24Model is mainly based on the Domino Theory and Swiss Cheese Model. The theoretical evolution of the 24Model and its applications are presented. 24Model can be applied to intelligent accident analysis with its precise definitions. The results of accident analysis were used to develop a safety training system. A quantitative measurement system of safety culture was designed using 24Model. Abstract: Systemic accident causation models are widely used in safety research. However, there exists a gap between research and practice. This paper introduces a popular systemic accident model (24Model) in China, describing its source and logical structure. Besides, the applications of 24Model in safety theoretical research and practice are examined based on statistics of publications and case study. The results show that the 24Model is mainly based on the domino theory and Swiss cheese model, and it is also influenced by the models of Bird and Stewart. It has been evolving into its sixth version. The systems thinking of 24Model was explained in the fifth and sixth versions. The main research topics of 24Model are accident analysis, safety management, and safety culture. As a formal method, 24Model has supported the development of an accident analysis and training system and a safety culture analysis process. In addition, 24Model can support safety science fundamental research, which facilitates the understanding of safety science and educational programs in this field. In the future, 24Model would provide a more accurate classification framework to support the intelligent accident analysis, company safety management, and education programs.